Novel Immune-Related Genetic Expression for Primary Sjögren's Syndrome - Cui, Jiajia; Li, Hui; Wang, Tianling; Shen, Qin; Yang, Yuanhao; Yu, Xiujuan; Hu, Huaixia (Frontiers in Medicine, 2022)
Objective: To identify novel immune-related genes expressed in primary Sjögren's syndrome (pSS). Methods: Gene expression profiles were obtained from the Gene Expression Omnibus (GEO) database, and differentially expressed genes (DEGs) were screened. The differences in immune cell proportion between normal and diseased tissues were compared, weighted gene co-expression network analysis was conducted to identify key modules, followed by a protein–protein interaction (PPI) network generation and enrichment analysis. The feature genes were screened and verified using the GEO datasets and quantitative real-time PCR (RT-qPCR). Results: A total of 345 DEGs were identified, and the proportions of gamma delta T cells, memory B cells, regulatory T cells (Tregs), and activated dendritic cells differed significantly between the control and pSS groups. The turquoise module indicated the highest correlation with pSS, and 252 key genes were identified. The PPI network of key genes showed that RPL9, RBX1, and RPL31 had a relatively higher degree. In addition, the key genes were mainly enriched in coronavirus disease-COVID-2019, hepatitis C, and influenza A. Fourteen feature genes were obtained using the support vector machine model, and two subtypes were identified. The genes in the two subtypes were mainly enriched in the JAK-STAT, p53, and toll-like receptor signaling pathways. The majority of the feature genes were upregulated in the pSS group, verified using the GEO datasets and RT-qPCR analysis. Conclusions: Memory B cells, gamma delta T cells, Tregs, activated dendritic cells, RPL9, RBX1, RPL31, and the feature genes possible play vital roles in the development of pSS.